# math

posted by .

Kahlil said that using the equation

(a + b)2 = a2 + 2ab + b2, , he can find a
similar equation for

(a − b)2 . Examine his argument. If it is correct, supply any
missing steps or justification; If it is incorrect point out why.

(a + b)2 = [a + (−b)]2
= a2 + 2a(−b) + (−b)2
= a2 − 2ab + b2
Mathematical Connections 5‐3
2. a.

• math -

Your calculations show that the 2 expressions are similar, but your Eq should be (a-b)^2.

## Similar Questions

1. ### math

42. Hosni gave the following argument that 2(a 1 b) 5 2a 1 2b, for all integers a and b. If the argument is correct, supply the missing reasons. If it is incorrect, explain why not. -a (b+a)= (-1)(a+b) = (-1)a+ (-1) b = a+ -b
2. ### algebra

Hosni gave the following argument that 2(a 1 b) 5 2a 1 2b, for all integers a and b. If the argument is correct, supply the missing reasons. If it is incorrect, explain why not
3. ### Algebra

Why does this happen? A=3 and b=2 A+b=c is the equation. Multiplying both sides of the equation makes the equation a^2+2ab+b^2 which is equal to a^2+ab-ac=-ab-b^2+bc Dividing by (a+b-c) we find a=-b or 3=-2 Why?
4. ### Math

Hosni gave the following argument that -(a + b) = -a + -b, for all integers a and b. If the argument is correct, supply the missing reasons. If it is incorrect, explain why not. - (a + b) = (-1) (a + b) = (-1) a + (-1) b = -a + -b
5. ### calculus

Find an equation for the surface consisting of all points P(x, y, z) equidistant from the point P(0, 1, 0) and the plane x = 3. Answer Choices: 1. y2 + z2 − 6x + 2y − 8 = 0 2. x2 + z2 + 6y − 2z − 8 = 0 3. y2 …
6. ### math 213

Kahlil said that using the equation he can find a similar equation for Examine his argument. If it is correct, supply any missing steps or justifications; if it is incorrect, point out why. = a2 - 2ab + b2 = a2 + 2a1-b2 + 1-b22 1a …
7. ### math

Hosni gave the following argument that -(a+b)=-a+-b for all integers a and b. If the argument is correct, supply the missing reasons. If it is incorrect, explain why. -(a+b)=(-1)(a+b) =(-1)a+(-1)b =-a+-b -(a+b)=(-1)(a+b)=(-1)a+(-1)b=(-a)+(-b)=-a+-b
8. ### math

Kahlil said that using the equation (a + b)2 = a2 + 2ab + b2, he can find a similar equation for (a - b)2. Examine his argument. (a - b)2 = [a + (-b)]2 = a2 + 2a(-b) + (-b)2 = a2 – 2ab + b2
9. ### Math - Equation of the circle

Find an equation of the circle whose endpoints of a diameter are (−3,6) and (5,−14). I tried to figure it out, but I'm not sure if my answer is correct. I got.. (x-2)^2 + (y + 4)^2 = 116 Any help would be great. Thank you!
10. ### Algebra

Find the missing coordinate to complete the ordered-pair solution to the given linear equation. 2x−3y=3 (a) (−3, ) (b) ( ,1)

More Similar Questions